2008
DOI: 10.1016/j.biomaterials.2008.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Bcl-2 as a proxy redox stimulus to enhance activity of non-viral redox-responsive delivery vectors

Abstract: Redox-sensitive non-viral delivery systems exploit intracellular reducing environment to improve the efficacy of the delivery of nucleic acids by selectively releasing the cargo in the subcellular space. Bcl-2 overexpression is frequently observed in human cancers and is closely associated with increased resistance to chemotherapy and radiotherapy. One of the biochemical alterations accompanying Bcl-2 overexpression is the increase in cellular glutathione (GSH) levels. In this study, we hypothesize that such i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…The total intracellular GSH content (i.e., both oxidized and reduced forms) was determined using a previously published enzymatic recycling method [19]. Briefly, 3×10 5 Panc-1 and Panc-28 cells were seeded in a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…The total intracellular GSH content (i.e., both oxidized and reduced forms) was determined using a previously published enzymatic recycling method [19]. Briefly, 3×10 5 Panc-1 and Panc-28 cells were seeded in a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…One hypothesis could be that the disulfide reduction is likely to have a smaller effect on low-molecular-weight nucleic acids due to a smaller influence of the polycation size on the unpacking rates. [78] REVIEW www.advmat.de…”
Section: Compartmentation Of Gshmentioning
confidence: 98%
“…Cellular GSH levels [21, 24], subcellular distribution of GSH [21], concentration of cell surface protein thiols [25] and population doubling time [21] were measured for all the cell lines. Intracellular GSH concentration was measured on reverse-phase ion-exchange Waters HPLC system and normalized to cell volume determined using Packed-Cell-Volume tubes using the protocol described by the manufacturer (MidSci).…”
Section: Methodsmentioning
confidence: 99%
“…We previously tested the effect of increased GSH levels associated with overexpression of Bcl-2 (an anti-apoptotic protein overexpressed in multiple human cancers). The results demonstrated that Bcl-2 overexpression can be utilized as a proxy redox stimulus to selectively enhance the activity of all four major classes of potential nucleic acid therapeutics, when delivered by redox-sensitive vectors [21]. …”
Section: Introductionmentioning
confidence: 99%